Bromoderma mimicking pyoderma gangrenosum caused by commercial sedatives. Issue 5 (28th October 2015) - Oda, Fumiko; Tohyama, Mikiko; Murakami, Akiko; Kanno, Kazuhisa; Sonobe, Naomi; Sayama, Koji
Abstract: Bromoderma is a rare skin disorder caused by bromide intake. It presents as single or multiple papillomatous nodules or plaques, and ulcers studded with small pustules on the face or limbs. The clinical features of bromoderma are similar to those of pyoderma gangrenosum. A 41‐year‐old Japanese woman was diagnosed with pyoderma gangrenosum 11 years prior to presentation. Pyoderma had repeatedly appeared over her entire body despite treatment. She also frequently complained of syncopal episodes. She was admitted to our hospital after loss of consciousness and an episode of generalized convulsion. Laboratory tests revealed a negative serum anion gap and hyperchloremia. Her serum bromide level was significantly elevated, suggesting bromide intoxication. The patient had a 10‐year history of high serum bromide levels. After the intake of bromide‐containing sedatives was stopped, there was no recurrence of pyoderma in the absence of treatment. In conclusion, this case was diagnosed as bromoderma with commercial sedative‐induced bromide intoxication. Although the US Food and Drug Administration have banned the use of bromides, over‐the‐counter (OTC) treatments containing bromides are still used in Japan and other countries. Long‐term use of OTC medicines containing bromvalerylurea may result in the development of bromoderma. If unclarified neurological or psychiatric symptoms are associated with pyoderma, we propose measurement of the patient's serum chloride concentration. Determination of hyperchloremia is helpful for the diagnosis of chronic intoxication with bromides.